Indícios de autoria em narrativas de estudantes de ensino médio - Monteiro, Isaura Maria de Carvalho (2009)
This dissertation analyses five narratives written by high-school students. The analysis applies concepts of discursive analysis; the theme involves aspects about the author and authorship. The choice of the corpus reflects an interest on “the writing of an author”, the one that presents peculiar traces. The writings of those “student authors”, in spite of having been produced in an institution – a school -, reveal characteristics of a literary text. The study begins with a general proposal to discuss alterity, reflecting on Amorim (2004), Bakhtin (1976), Benveniste (1995) and Authier-Revuz (2004). Then, the problem concerning the author – in the present and in the past – as well as Barthes’ (1984), Foucault’s (1997, 2001, 2006) and Bakhtin’s (1976, 1981, 1995, 1998, 2003) ideas are discussed. The theme reveals various aspects. Authorship is widely discussed, and Bakhtin is pointed out as the theoretic conductor of the study. The bakhtinian analysis relies on the “indiciary methodology” (GINZBURG, 1989), a qualitative procedure which is considered adequate for the proposed analysis. The ways discourse is organized (CHARAUDEAU, 2008), as well as the composition of enunciations as architectonic (BAKHTIN, 1998) are also discussed. The texts are analysed through bakhtinian concepts in connection with authorship, genders and style: at first, the composition of the theme, its valuation and signification in the narrative context (BAKHTIN, 1976, 1995, 1998) are discussed. Then, it’s the turn of alterity and authorship. Thus, the question is: Were traces of authorship detected inside the students’ narratives? Through the analysis based on bakhtinian concepts of esthetic creation, it is possible to affirm that the “work of authorship” has been shown throughout the students’ written production.